DIFFERENT FORMS OF OBSESSION WITH FALSE RELIGIOUS INFORMATION IN ADOLESCENCE - Bekkieva Nargiza Rajabbaevna (The Conference Hub, 2025)
There are different manifestations of obsession with fake religious information in adolescence, as this age group is particularly vulnerable to online manipulation. In the process of self-awareness and understanding, adolescents often turn to external sources of information, including social networks full of fake or inaccurate religious content. This bias is related to cognitive development, emotional needs, and a lack of critical thinking skills. The study shows how easily adolescents fall prey to fake religious information and the importance of developing critical thinking and religious education in dealing with this issue.
Keywords: Adolescents' addiction, false religious information, psychological aspects, cognitive development, emotional embarrassment, critical thinking, religious education, online manilpulation, self-awareness, influence of social media.